2023
DOI: 10.1007/s44217-022-00022-x
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the activities and outcomes of digital teaching and learning of practical skills in higher education for the social and health care professions: a scoping review

Abstract: Higher education for health care professionals faces numerous challenges. It is important to develop and apply methods supporting education, especially the practical skills. This scoping review aimed to explore the activities and learning outcomes of digital technology in practical skills teaching and learning in higher education for the social and health professions. Scoping review recommendations and the PRISMA-ScR checklist were applied. Randomized controlled trials published between 2016 and 2021 involving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 76 publications
0
4
0
Order By: Relevance
“…However, this approach assumes that all students and teachers have access to the digital tools. Institutions that consider this model must ensure robust support systems to overcome potential technological barriers ( Söderlund et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, this approach assumes that all students and teachers have access to the digital tools. Institutions that consider this model must ensure robust support systems to overcome potential technological barriers ( Söderlund et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies from different countries have shown that despite efforts to increase and improve digital teaching and learning in universities in different cultures, both teachers and students use of digital technology is rather limited (e.g., Bond et al, 2018;Amhag et al, 2019;Ferede et al, 2023;Söderlund et al, 2023). It is claimed that teachers' ICT training should take adequate time to learn and reflect upon new skills and knowledge, short-term training seems to be inefficient (Inamorato dos Santos et al, 2019).…”
Section: The Use Of Digital Tools In Teachingmentioning
confidence: 99%
“…In addition, it is argued that performing practical skills on real patients can help students gain deeper knowledge when compared with the other options [ 12 ]. Whereas gaining practical skills in traditional teaching includes components such as physical examination of patients, history taking and performing various procedures [ 13 ], this was no longer an option in this new reality. Due to the pandemic, the transition from traditional instructional settings to online environments in gaining practical skills, with the help of digital technologies, has created a new field of experience for both academic staff and students.…”
Section: Introductionmentioning
confidence: 99%
“…Despite all the challenges, the COVID-19 pandemic offered tremendous opportunities for online teaching and the utilization of digital technologies. Online education techniques have created new opportunities for teaching and learning in more creative ways compared to what is offered in a typical classroom setting [ 1 , 13 ]. An in-depth understanding of this period is needed to take advantage of these opportunities.…”
Section: Introductionmentioning
confidence: 99%